2020
DOI: 10.3389/fmicb.2020.01840
|View full text |Cite
|
Sign up to set email alerts
|

Oral Microbiome and SARS-CoV-2: Beware of Lung Co-infection

Abstract: The new coronavirus SARS-CoV-2, the cause of COVID-19, has become a public health emergency of global concern. Like the SARS and influenza pandemics, there have been a large number of cases coinfected with other viruses, fungi, and bacteria, some of which originate from the oral cavity. Capnocytophaga , Veillonella , and other oral opportunistic pathogens were found in the BALF of the COVID-19 patients by mNGS. Risk factors such as poor oral hygiene, cough, increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
173
2
31

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(218 citation statements)
references
References 147 publications
4
173
2
31
Order By: Relevance
“…Nevertheless, the microbial composition plays a very important role as being an indicator of either healthy or disease status ( Wang et al., 2017 ). Several studies investigated if the microbiota could modify the risk of developing the COVID-19 by evaluating its complications particularly at respiratory level ( Bao et al., 2020 ; De Maio et al., 2020 ; He et al., 2020 ; Khatiwada and Subedi, 2020 ; Shen et al., 2020 ). The recent evidences reported that some microorganisms are associated with SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the microbial composition plays a very important role as being an indicator of either healthy or disease status ( Wang et al., 2017 ). Several studies investigated if the microbiota could modify the risk of developing the COVID-19 by evaluating its complications particularly at respiratory level ( Bao et al., 2020 ; De Maio et al., 2020 ; He et al., 2020 ; Khatiwada and Subedi, 2020 ; Shen et al., 2020 ). The recent evidences reported that some microorganisms are associated with SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…The latter results in a systemic damage, with multiorgan injury, particularly in patients with severe COVID-19 ( Abu Hammad et al., 2020 ). Recent publications showed the possible relationship between gut, lung, nasopharyngeal, or oral microbiome and COVID-19 ( Antunes et al., 2020 ; Bao et al., 2020 ; De Maio et al., 2020 ), but very little is known about it. Therefore, we aimed to verify if the nasopharyngeal microbiome could influence both the development of COVID-19 and the severity of its symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The oral cavities are known as a notable reservoir of SARS-CoV-2 [ 111 ]. Since the oral microbiota interacts with SARS-CoV-2, efficient oral health care efforts are needed to reduce severe SARS-CoV-2 infections [ 112 ]. The microbiota in the human body, such as nasal channels, oral cavities, skin, gastrointestinal tract, and urogenital tract, are important in physiological process, immunity, and nourishment [ 113 ].…”
Section: Respiratory Microbiota Dysbiosis and Covid-19mentioning
confidence: 99%
“…Observing overall shifts in the bacterial and fungal community of sinus diversity was shown to be attributed to a compound of personal, seasonal, and annual changes [ 120 ]. Oral opportunistic pathogens like Capnocytophaga and Veillonella were found in the bronchoalveolar lavage (BAL) sample of the COVID-19 patients [ 112 ]. The poor oral hygiene, cough, raised inhalation conditions, and ventilation cause a transmission route for oral microbiota to penetrate the lower respiratory tract and cause respiratory disorders [ 112 ].…”
Section: Respiratory Microbiota and Covid-19 Transmissionmentioning
confidence: 99%
“…In that sense, the upregulation of key genes belonging to the IL-10 pathway observed in our analysis ( Figure 2 C), previously demonstrated to play a deleterious role in innate resistance to systemic aspergillosis [ 37 ], constitutes an illustration of how such “enhanced” state of inflammation could contribute to increasing severity. Our results, which give a first glimpse of the interactions between the host cell and SARS-CoV-2/ Aspergillus , are to be placed in the broader and more complex context of the microbiota, which could also play a regulatory role in the severity of the pathology [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%